Politicians' use of Facebook during elections: Use of emotionally-based discourse, personalization, social media engagement and vividness. Issue 5 (17th September 2018) - Bronstein, Jenny; Aharony, Noa; Bar-Ilan, Judit
Abstract : Purpose: The purpose of this paper is to understand the use of Facebook by Israeli party leaders during an election period by examining four elements: the type of Aristotelian language of persuasion; the level of online engagement measured by three different types of feedback: likes, comments and shares; the use of personalization elements as engagement strategies; and the vividness features used in the post (text, photographs and video). Design/methodology/approach: All of the posts from the Facebook pages of ten Israeli party leaders were collected for 45 days prior to the 2015 general elections. The number of posts, likes, comments and shares in each post were captured and the data were analyzed looking for elements of Aristotelian persuasion and of online engagement with the users. Findings: The dominance of pathos was a salient element in the data demonstrating the politicians' need to create an affective alliance with the public and it was the element that resulted in a higher number of likes, shares and comments. Only a few relationships were found and these do not point to a clear relationship between multimedia use and social media engagement. The interactive, open and free nature of social networking sites contributes to their development as a new type of political podia that allow politicians to produce a different kind of political communication. Instead of using these sites as platforms to disseminate their ideas, plans and strategies, politicians focus their interactions with the audience on the creation and maintenance of affective alliances. Originality/value: The study contributes to the existing literature on the subject by examining four characteristics of the politicians' personal profiles on social networks simultaneously while most of the past studies have focused on only one or two of these characteristics.